The Development of Interactive Games for Covid-19 Prevention Using Indonesian Health Protocols - Arrahman Kaffi; Maulana Rizqi; Gerardo AK Laksono; Alvin Julian; Agustinus Bimo Gumelar (Department of Informatics, Universitas Islam Negeri Syarif Hidayatullah, 2022)
COVID-19 has become a virus spreading quickly across the world.The government of Indonesia also immediately adjusted theconditions to minimize the spread of the COVID-19 virus byimplementing the health protocols 5M namely, wearing a mask,washing hands, keeping distance, avoiding crowds, and reducingmobility. With the advancement of technology, games can be used aseducational media to support users learning processes and increasetheir knowledge. Therefore, we conducted a study using the learningsupport media, namely interactive games based on a personalcomputer platform with the Windows operating system to help theusers understand the prevention of the COVID-19 virus byimplementing health protocols. This study proposes using a structurefor the iterative cycle process called the ADDIE model framework andusing the Unity game engine for its game development tools. Tomeasure the feasibility of interactive games as educational media, weuse the System Usability Scale method. Based on the applicationtesting of 50 respondents, interactive games get a score of 90 on a scalethat is acceptable. The results also indicate that interactive games aseducational media will improve the users learning process andmotivation about implementing the health protocols.